Water Availability Analysis of the Cilamaya Watershed Using the F.J. Mock Method: Analisis Ketersediaan Air DAS Cilamaya Berdasarkan Metode F.J. Mock - Shafa Camilla Az-zahra; Wilma Nurrul Adzillah; Zulfa Amala (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Water availability is a critical factor in sustainable watershed management, particularly in areas experiencing climatic variability and land-use pressure such as the Cilamaya Watershed in West Java, Indonesia. This study aims to analyze water availability in the Cilamaya Watershed using the F.J. Mock hydrological method based on climatological data and watershed characteristics. The data used include rainfall, air temperature, relative humidity, wind speed, and sunshine duration, which were processed to estimate the water balance and monthly discharge. The results indicate that river discharge in the Cilamaya Watershed exhibits strong seasonal fluctuations, with high flows during the rainy season and a sharp decline during the dry season. During several dry months, the model results show water deficit conditions, as low rainfall is unable to compensate for water losses through evapotranspiration. The dependable flow analysis (Q90) reveals that reliable water availability occurs mainly during the rainy season, while in the dry season the watershed is unable to guarantee a sustainable minimum flow. These findings demonstrate that the Cilamaya Watershed has a high level of hydrological vulnerability, highlighting the need for adaptive water resources management strategies, particularly through strengthening infiltration functions and regulating water use during dry periods.